O sertanejo e Lourenço: a construção mítica do herói regional - Costa, Kamila Jéssick Duarte da (2016)
This dissertation has the purpose of analyzing the construction of the Brazilian regional hero by a comparative study among the novels O sertanejo, by José de Alencar, and O matuto and Lourenço, by Franklin Távora. A parallel was drawn between the protagonists of the referred wefts, observing similarities, tensions, contrasts and dialogues in their constructions, as well as reflecting about their relations with the sociocultural context in which they are inserted. Because of attempting to create, affirm and consolidate a national literary tradition, José de Alencar and Franklin Távora wrote novels that portrayed an exuberant nature and the sociocultural aspects of certain localities of our country, creating regional heroes compatible with reality presented in narratives. This study is divided into three chapters. In the first, we emphasize the hero’s mythical character and its incidence in literary scope, what brings the necessity of discussing the novel hero’s construction, with prominence to the romantic hero and its construction in the national scenario. In the second, we discuss about regional line in the Brazilian literary tradition, more specifically, in the end of the romantic period. Finally, the last chapter deepens our discussions related to each author’s literary projects, their influences in the creation of these novels and in their respective heroes, but, specially, we demonstrate these heroes’ problematic character. This dissertation, so, aims to better understand the novels analyzed by these two authors, contributing the studies relating to these literary works and to the construction of their respective heroes.